A dynamic key management and secure data transfer based on m-tree structure with multi-level security framework for Internet of vehicles. Issue 1 (31st December 2022) - Lin, Hua Yi; Hsieh, Meng-Yen
Abstract : Nowadays, broadband wireless networks and 5G have improvements in the quality and dependability of network services for high-speed mobile vehicles. Within an open communication environment on the Internet of vehicles named IoV, personal details will be revealed on the Wi-Fi network. Considering information security and privacy, this research concentrates on how to protect secure information transmission in real time through IoV, and also wants to avoid illegal vehicles, passers-by or drivers from joining connection and planting or altering significant data. This research provides a multilevel security infrastructure with M-tree based elliptic curve digital signature algorithm (ECDSA) for securing data transmission in both IoV and cloud environments. While transmitting, this study provides several flexible and scalable schemes to manage security issues, which dynamically adjust the framework depending on the rapidly changing IoV topology and speed up the time to synchronise the reconstruction of the system key, and decrease the quantity of phases to resynchronise the system key. Moreover, most research of key management without secure data transmission, we integrate the M-tree key management with secure data transmission to achieve the secure IoV. Simultaneously, the provided key management for the multi-level security is quite appropriate to adaptable and expandable IoV.